1993
DOI: 10.1002/1097-0142(19930801)72:3<887::aid-cncr2820720338>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Postirradiation sarcoma of the head and neck

Abstract: Background. With improvement in survival after cancer treatment, it is becoming increasingly important to study treatment‐related morbidity and mortality. Sarcoma can develop in the irradiated field after radiation therapy. The authors performed a study to estimate the risk, and compared the risk of sarcoma after radiation therapy with that of other treatment modalities used against cancer. Methods. Between 1955 and 1988, 229 patients with sarcoma of the head and neck were seen at the University of California,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 46 publications
5
63
0
7
Order By: Relevance
“…Patients undergoing a full course of RT for NPC received a dose equivalent to about 66 Gy or more, and most sarcomas in this series arose in the maxillary region, the middle and posterior part of which received this full radiation dose. The development of sarcomas after radiation exposure for both benign and malignant conditions is well established in the head and neck with a reported latency period from a few months to 65 years [19,20]. For those arising after treatment for NPC, the reported range is 6-27 years with a mean of 13 years [8], although in this series they arose after 4-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing a full course of RT for NPC received a dose equivalent to about 66 Gy or more, and most sarcomas in this series arose in the maxillary region, the middle and posterior part of which received this full radiation dose. The development of sarcomas after radiation exposure for both benign and malignant conditions is well established in the head and neck with a reported latency period from a few months to 65 years [19,20]. For those arising after treatment for NPC, the reported range is 6-27 years with a mean of 13 years [8], although in this series they arose after 4-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years). [3][4][5][6][7][8][9][10][11][12][13]34 The best survival outcome was reported by Tabone et al, 35 who reported that the OS and eventfree survival rates for 23 patients with radiation-related osteosarcoma at 8 years were 50% and 41%, respectively.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…Mark et al reported the poor survival of patients with RIS, including a 5-year OS rate of 8% for those with sarcomas in the head and neck. 34 In addition, the survival rates for patients with RIS in the head and neck was poor relative to the rates for patients with de novo sarcomas in head and neck. In a study by Patel et al, 10 the 5-year diseasefree survival rate in the RIS group was significantly worse than that in the de novo group (31% vs 54%).…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…The post-irradiated EAC carcinoma has been infrequently reported [18][19][20][21][22][23][24][25]. Lo et al [5] reported that the incidence of EAC carcinoma in the post-irradiated NPC population was 1000 times greater than the reported incidence of primary EAC carcinoma in the general population.…”
Section: Discussionmentioning
confidence: 99%